"UNUSUAL" TISSUES AND SAMPLE COLLECTION STRATEGIES ON EXHUMED BODIES. Issue 1 (December 2019) - Agostini, V.; Gino, S.; Inturri, S.; Marino, A.; Staiti, N.; Sticchi, M.; Chiti, E.; Linarello, P.; Gentile, G.; Primignani, P.; Giriodi, M.; Bailo, P.; et al.
Abstract: The choice of soft or hard tissues to be sampled in case of exhumation of corpses for identification purposes or family relationship testing is based on the degradation conditions of the corpse: the more the corpse is degraded, the less DNA is expected to be retrieved from soft tissue. Therefore, the choice of the "best" tissue samples usually falls on teeth and bones in these "difficult" cases, even though the DNA extraction procedure requires time and effort and it can often result in unexpected, negative results. We here present the results of a daily practice survey that shows that it is possible to obtain good results even on DNA extracted from tissues that appear to be less "appealing" to the examiner by performing "simple" corneal/scleral swabs along with cartilage. While DNA extracted from cartilage has been already described, to our knowledge there is no evidence of publications in the scientific literature dealing with cornea/sclera as a source of DNA in the forensic laboratory. The obtained results demonstrate that it may be advisable to consider other tissues which bear the potential of returning good profile results despite not appearing particularly useful and better control of contamination.